Промоција на производите на пазарот на алкохолни пијалоци во Република Македонија, споредено со земјите-членки на Европската Унија - Јаќоска, Николина (Економски факултет, УКИМ, Скопје, 2012)
Alcohol and alcoholic beverages are known to mankind since ancient times, when social life evolved in more civilized forms. What remains to be the greatest and continuing challenge for manufacturers and companies dealing with alcoholic beverages is - their sales. While the content and structure of alcoholic beverages are relatively unchanged as far as we can recall, what is constantly changing is the most relevant factor - the ultimate purchaser, the consumer. The specific characteristics of alcoholic beverages has always triggered controversy in social trends and different reactions aimed at controlling their trade movement and their ultimate commercial use. Therefore, the development and innovation in the modern alcohol industry is based primarily on the skills of communication experts, rather than on the production process. Actual socio-economic and regulatory relations transform the alcohol industry into a promotional industry. The promotion of alcoholic beverages in modern conditions is a real challenge and motivates search for a creative expression of the promotional message that must pass through numerous regulatory and socially acceptable filters until it reaches the audience. The rapid development of almost unbelievable ways of communication is in favor of alcohol promotion, since it is done on a less visible, more subtle level. Promotion of alcoholic beverages in the Republic of Macedonia shows signs of leaving the established framework of traditional marketing. Many innovative promotional activities for global alcohol brands are accepted and applied on our market, whether as a part of the global campaign for a particular brand or independently conducted by domestic manufacturers and distributors of alcohol. It becomes obvious that Macedonian companies that work in the alcohol industry take the initiative and push for continuous improvement and adaptation of promotional activities to the types and forms that are relevant and existing in the global and European market.
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: promotion, alcoholic beverages, alcohol industry, integrated marketing communication, distributors of alcoholic beverages, a global campaign for alcohol brands, promotion over the line, below the line promotion